2023
DOI: 10.1111/jocd.15966
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of biostimulatory effects after polydioxanone thread insertion in a pig model

Diya Su,
Shiwei Wang,
Tong He
et al.

Abstract: BackgroundPolydioxanone (PDO) threads have been widely used to tighten and lift the facial soft tissue.ObjectiveThis research aims to determine the collagenation and inflammation changes that occur in the adipose tissue over time when different types of threads are implanted.Methods & MaterialsThree threads types, PDO, poly glycolic‐co‐lactic acid (PGLA), and nylon, were inserted in the subcutaneous fat of 12‐month‐old Bama miniature pigs. Collagen production and inflammatory response were evaluated by hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The literature extensively explores the role of PDO threads in stimulating collagen formation, with numerous studies supporting this effect. [14][15][16] For instance, Kim et al 17 In conclusion, our case presents the effectiveness of addressing subzygomatic arch depression through the application of volumizing PDO threads, showcasing it as an effective and safe technique in facial rejuvenation. The patient's satisfaction with the outcomes highlights the efficacy of this approach in achieving the desired aesthetic improvements.…”
Section: F I G U R Ementioning
confidence: 68%
See 1 more Smart Citation
“…The literature extensively explores the role of PDO threads in stimulating collagen formation, with numerous studies supporting this effect. [14][15][16] For instance, Kim et al 17 In conclusion, our case presents the effectiveness of addressing subzygomatic arch depression through the application of volumizing PDO threads, showcasing it as an effective and safe technique in facial rejuvenation. The patient's satisfaction with the outcomes highlights the efficacy of this approach in achieving the desired aesthetic improvements.…”
Section: F I G U R Ementioning
confidence: 68%
“…The literature extensively explores the role of PDO threads in stimulating collagen formation, with numerous studies supporting this effect. 14 , 15 , 16 For instance, Kim et al. 17 compared the collagen‐producing effects of powdered PDO with poly‐L‐lactic acid, finding that powdered PDO injections induce collagen formation more effectively in a murine model.…”
mentioning
confidence: 99%
“…In a study by Su et al 10 conducted on pigs, PDO threads were found to induce mild inflammation and stimulate collagen production, peaking at 12 weeks and persisting until 48 weeks before complete degradation. Additionally, PDO threads exhibited a fibrous bridging effect, enhancing tissue connectivity and thickness without causing severe side effects such as foreign body granuloma.…”
Section: Discussionmentioning
confidence: 99%